Empowering smallholder farmers’ organizations through non-public extension service providers: A case study and lessons from Mozambique - Babu, Suresh Chandra; Gêmo, Hélder (International Food Policy Research Institute, 2019)
The role and impact of non-state extension services providers have not been studied adequately. In this paper, we assess the performance of the non-State extension service provision through farmers organization (FOs) in Mozambique. Using participating methods, focused group discussions, and key informant interviews, we provide an assessment of extension services provision to FOs. The result indicates only 3% of the 1264 surveyed FOs were categorized as "type A", the highest FOs rating scale used by services providers (SPs) in the three regions of the country. Effective monitoring and evaluation (regular, analytical, participatory) at field level and close working interaction between the Public Agricultural Extension Services (PAES) and the SPs were of paramount importance to track the progress made in empowering the FOs. SPs' pro-activeness and competence were critical factors to adequately address the various training needs of the different categories of FOs and local services providers. SPs' financial autonomy was key to compensate for the delays in the disbursements by the PAES. The selection criteria for the participating farmers (trainees) from targeted FOs makes a difference. Younger and more literate farmers (including women) have shown greater motivation and engagement in the training sessions. Outsourcing can be a valuable alternative for the provision of extension services if it targets specific intervention areas (for example, training for FOs), a limited number of activities, well-defined deliverables (including quality and sustainability issues) and timelines. Post-training (and post-project) actions at the policy level and extension services providers are required to contribute to the sustainability of the investment made. Based on these findings, the paper documents several operational lessons from the implementation of the program.